Investigating the relationship between motivation and self-regulated learning towards physics subject among foundation students / Siti Aisyah Zawawi … [et al.] - Zawawi, Siti Aisyah; Abd.Latif, A’bir Wardati; Ku Mohd Noh, Ku Siti Syahidah; Arom Karoman, Nor Fadzilah; Mohd Mustapha, Haslinawati; Kamaruzaman, Nadiah (Universiti Teknologi Mara Cawangan Pulau Pinang, 2024)
Physics is evaluated as one of the most challenging subjects among students in the science field during their high school years and becomes more difficult in college or foundation level. Due to various factors incorporated in this study, which investigates the relationship between foundation students’ motivation and self-regulated learning toward physics subjects, certain students are unable to receive exceptional results or perform poorly. The study's target group encompassed all foundation students enrolled in physics courses from two Malaysian institutions. The survey adapted from Tuckman's model was used as the instrument for data collection and was created via Google Forms using a 3-Likert scale. This study focuses on students’ perspectives, motivation, and self-regulated learning practices for physics subjects. A total data of 262 respondents was successfully obtained and transferred to IBM Statistics (Statistical Package for the Social Sciences) Version 28 for analysis. A conclusive and agreeable result of students' perspectives from the survey is that students themselves must give their best effort to comprehend physics with a very high mean of 2.8740. The greatest mean of 2.6870 for students' motivation indicated that the lecturer's support was a driving force behind their desire to learn. However, the greatest mean value of 2.6794 was found for self-regulated learning suggesting that even if students dislike the subject of physics, they still need to put in a lot of effort to get decent grades. The final findings showed a strong positive correlation, (r = .634*) and (p = .000) between students' perspectives and cognitive strategy used among students towards physics subjects. Moderate positive correlations were obtained for both correlations between motivation and cognitive strategy used (r = .464*) and (p = .000).